Facile Synthesis of FePS3 Nanosheets@MXene Composite as a High-Performance Anode Material for Sodium Storage - Yonghao Ding; Yu Chen; Na Xu; Xintong Lian; Linlin Li; Yuxiang Hu; Shengjie Peng (Nano-Micro Letters, 2020)
Abstract Searching for advanced anode materials with excellent electrochemical properties in sodium-ion battery is essential and imperative for next-generation energy storage system to solve the energy shortage problem. In this work, two-dimensional (2D) ultrathin FePS3 nanosheets, a typical ternary metal phosphosulfide, are first prepared by ultrasonic exfoliation. The novel 2D/2D heterojunction of FePS3 nanosheets@MXene composite is then successfully synthesized by in situ mixing ultrathin MXene nanosheets with FePS3 nanosheets. The resultant FePS3 nanosheets@MXene hybrids can increase the electronic conductivity and specific surface area, assuring excellent surface and interfacial charge transfer abilities. Furthermore, the unique heterojunction endows FePS3 nanosheets@MXene composite to promote the diffusion of Na+ and alleviate the drastic change in volume in the cyclic process, enhancing the sodium storage capability. Consequently, the few-layered FePS3 nanosheets uniformly coated by ultrathin MXene provide an exceptional reversible capacity of 676.1 mAh g−1 at the current of 100 mA g−1 after 90 cycles, which is equivalent to around 90.6% of the second-cycle capacity (746.4 mAh g−1). This work provides an original protocol for constructing 2D/2D material and demonstrates the FePS3@MXene composite as a potential anode material with excellent property for sodium-ion batteries.